Review on Sanskrit Sandhi Splitting using Deep Learning Techniques (Journal of Information Technology and Digital World, 2024)
A procedure called sandhi is used in Sanskrit to join short words (morphemes) to create compound words. A composite word are broken down into their component morphemes by a process known as sandhi splitting. This study focuses on several performance technologies and methodologies used to perform the above operation on Sanskrit sentences. Various approaches were identified for the problem from the literature survey. Initial approaches involved use of Finite State Transducers. Earlier the approaches introduced to increase accuracy include use of mathematical models and various optimality theories. Graph based approaches and parser based techniques were introduced later. With the advancement of deep learning techniques Recurrent Neural Networks, Long-Short Term Memory models and Double decoder models were adopted which involved training machine learning models through neural networks and classifier algorithms. Bidirectional LSTM models with attention mechanism, transformer based models and large language models like BERT were the most recent methodologies adopted and proved to be of higher accuracy and performance.
Keywords: Deep learning; Natural Language processing; BiLSTM; Seq2seq models; RNN